Child Sex Ratio and It’s Socio-Demographic Correlates: A Cross Sectional Study in An Urban Area of Eastern Maharashtra - Shewte, Mamta K; Andurkar, Smita P (National Journal of Community Medicine, 2013)
Background: Sex ratio is an important social indicator to measure the extent of prevailing equity between males and females in a society. Objective: The Objective of the study was to find Child Sex Ratio (CSR) in the urban area of Aurangabad, Maharashtra and socio‐demographic factors affecting it. Methods: The present study is community based cross sectional study which involved house to house interview of mothers of 0-6 year children from urban area of Aurangabad. Information regarding all children born in last 6 years, their date of birth, birth order and demographic information of family was noted. Results: Overall child sex ratio of study area was 853. The highest child sex ratio was obtained for (CSR 1255) Muslim religion, (CSR 2667) when father studies up-to primary school, (CSR1778) when mother was illiterate and (CSR 1000) for class V and III socio-economic status. Least CSR 605 was obtained when the families have all females in previous birth order. Conclusion: This part of country or Maharashtra has lower CSR than national average. There are demographic factors like socio-economic status, education status of parents, religion and previous birth order, which influence CSR. There is less girl child insubsequent birth order, especially when the previous born child is female.